Dry Films and Laminates
Patent Information
- Application Number
- JP2020159985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-09-24
AI Technical Summary
【0013】 本発明によれば、フッ素が一定量以下のポリイミドに特定のエポキシ化合物を組み合せて樹脂層を形成したドライフィルムとすることにより、ガラス基板/樹脂層の積層体とした場合であっても、平坦性や高級感といった質感を維持しつつ、湾曲(反り)が無く、ガラス基板と樹脂層との密着性に優れ、且つ表面硬度や耐衝撃性にも優れる積層体が得られるドライフィルムを実現することができる。
Smart Images

Figure 0007645622000014 
Figure 0007645622000015 
Figure 0007645622000016
Abstract
Description
[Technical field]
[0001] The present invention relates to a dry film, and more particularly to a dry film that can be suitably used in the manufacture of a glass substrate / resin layer laminate, etc., as a cover window for a flexible display element. [Background technology]
[0002] In the field of electronic devices such as display elements such as liquid crystal displays (LCDs) and organic light-emitting diode displays (OLEDs) and electronic paper, flexible panels that have flexibility have begun to be adopted in addition to conventional flat panels. In particular, in recent years, the development of electronic devices equipped with bendable displays has progressed.
[0003] For the cover window of the flexible device as described above, the use of organic polymer materials such as polyimide instead of the conventional glass substrate has been proposed and has been put to practical use in some cases. However, since these polymer materials are inferior in rigidity and hardness to glass substrates, there are problems in that when used in a flexible panel, repeated bending can cause wrinkles and twists, and the surface can be easily scratched.
[0004] It has also been proposed to make the conventional glass substrate into an ultra-thin glass substrate of about several tens of microns, which can be bent while maintaining the flatness and luxurious feel of a display panel. Although ultra-thin glass has a certain bending radius, it has problems such as low compressive strength and impact resistance, which are inherent properties of glass. Therefore, in recent years, attempts have been made to use chemically strengthened ultra-thin glass.
[0005] However, although chemically strengthened ultra-thin glass is superior to ordinary ultra-thin glass in terms of compressive strength, bending strength, impact resistance, etc., it is inferior in puncture resistance (resistance to breakage when pressed with a sharp object). Therefore, in practice, a structure has been proposed in which chemically strengthened ultra-thin glass is sandwiched between a protective film such as a polyester film, with a flexible adhesive interposed between them.
[0006] Incidentally, in the technical field of display substrates, the use of a composite substrate in which a polyimide resin layer is laminated onto a glass substrate has been proposed as a material that combines water vapor barrier properties with flexibility (for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2002-534305 [Patent Document 2] Special Publication No. 2015-533685 [Patent Document 3] JP 2019-214159 A Summary of the Invention [Problem to be solved by the invention]
[0008] For applications such as cover windows for displays used in flexible devices, laminates in which a resin film is laminated on a bendable ultra-thin glass have been proposed. However, as described above, soft materials are used for the resin film or adhesive in terms of adhesion to the ultra-thin glass and shock absorption. Therefore, when used as a cover window, there are problems such as insufficient surface hardness, resulting in scratches and dents on the display surface, and the loss of texture such as flatness and a luxurious feel, which are advantages of using ultra-thin glass. In addition, there are problems such as the need for a process of bonding the ultra-thin film and the resin film via an adhesive, and the need for a certain thickness to give the adhesive shock absorption, making it impossible to reduce the total thickness of the cover window.
[0009] In the course of intensive research into the above-mentioned problems, the inventors focused on polyimide, which has excellent transparency, and produced a laminate of a glass substrate / polyimide layer by applying polyimide varnish to a glass substrate and drying it. The inventors found that the laminate had both high surface hardness and high impact resistance. However, when they tried to produce a laminate of an ultra-thin glass substrate / polyimide layer in the same manner, the inventors noticed a new problem that the laminate curved due to drying shrinkage when drying the coating film of the polyimide varnish. In order to prevent the laminate from curving, the inventors tried to make a polyimide varnish into a dry film and laminate a polyimide layer onto an ultra-thin glass substrate using the dry film, but they found that this method had a new problem in that sufficient adhesion between the polyimide layer and the ultra-thin glass substrate was not obtained. In particular, the adhesion was insufficient for fluorinated polyimides, which have excellent transparency.
[0010] The present invention has been made in light of these problems, and its object is to provide a dry film that can easily and simply produce a glass substrate / resin layer laminate without using an adhesive, and that can provide a laminate that is free of curvature (warping) while maintaining texture such as flatness and a luxurious feel, has excellent adhesion between the glass substrate and the resin layer, and also has excellent surface hardness and impact resistance. [Means for solving the problem]
[0011] The present inventors have further conducted intensive research in order to provide a dry film that can solve all of the above problems, and have found that by forming a dry film by combining a specific epoxy compound with a polyimide having a certain amount of fluorine or less to form a resin layer, the resulting glass substrate / resin layer laminate maintains texture such as flatness and a luxurious feel, while also exhibiting excellent adhesion between the glass substrate and the resin layer, and excellent surface hardness and impact resistance. The present invention has been completed based on this finding. That is, the gist of the present invention is as follows.
[0012] [1] A dry film comprising a substrate and a resin layer releasably provided on the substrate, The resin layer comprises a polyimide having a fluorine content of 25% by mass or less, and an epoxy compound having an epoxy equivalent of 1000 g / eq or less and a molecular weight of 10,000 or less. [2] The dry film according to [1], wherein the polyimide has a YI value of 5.0 or less when made into a single layer film having a thickness of 50 μm. [3] The dry film according to [1] or [2], wherein the polyimide has a haze of 2.0 or less when made into a single layer film having a thickness of 50 μm. [4] The dry film according to any one of [1] to [3], wherein the epoxy compound has a softening point of 150° C. or lower. [5] The dry film according to any one of [1] to [4], wherein the epoxy compound is contained in an amount of 1 to 50 mass % based on the total amount of solids in the resin layer. [6] The dry film according to any one of [1] to [5], wherein the resin layer further contains a bluing agent. [7] A laminate comprising a glass substrate and a resin layer provided in contact with one of the main surfaces of the glass substrate, The resin layer is a laminate comprising the resin layer of the dry film according to any one of [1] to [6]. [8] The laminate according to [7], wherein the glass substrate is chemically strengthened glass. [9] The laminate according to [7] or [8], which is used as a cover window for a flexible display element.
[10] A method for producing a laminate including a glass substrate and a resin layer provided in contact with one of the main surfaces of the glass substrate, comprising: [1] to [6] are attached to one of the main surfaces of a glass substrate so that the resin layer of the dry film is in contact with the main surface of the glass substrate; peeling the base material from the dry film to form a resin layer on the glass substrate; The resin layer is heated to a temperature equal to or higher than the softening point temperature of the epoxy compound. A method for producing a laminate, comprising: Effect of the Invention
[0013] According to the present invention, by forming a dry film by combining a polyimide having a certain amount of fluorine or less with a specific epoxy compound to form a resin layer, it is possible to realize a dry film that, even when used as a laminate of a glass substrate / resin layer, maintains the texture such as flatness and a luxurious feel, is free of curvature (warping), has excellent adhesion between the glass substrate and the resin layer, and provides a laminate that is also excellent in surface hardness and impact resistance. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view showing an embodiment of a dry film according to the present invention; [Diagram 2] FIG. 4 is a schematic cross-sectional view showing another embodiment of the dry film according to the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing an embodiment of a laminate according to the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another embodiment of a laminate according to the present invention. [Diagram 5] FIG. 4 is a schematic cross-sectional view showing another embodiment of a laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Dry film] The dry film according to the present invention will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing one embodiment of the dry film according to the present invention. The dry film 1 according to the present invention includes a substrate 10 and a resin layer 20 provided on the substrate 10. In the present invention, in order to prevent dust and the like from adhering to the surface of the resin layer 20 when the dry film is formed, and in consideration of the handling of the dry film 1, a protective film 30 may be further provided on the surface of the resin layer 20 opposite to the surface that contacts the substrate 10, as shown in FIG. 2. Each component constituting the dry film according to the present invention will be described below.
[0016] <Base material> The substrate can be any substrate that can support the resin coating film when forming the resin layer described below, and can be suitably used, for example, a polyester film such as polyethylene terephthalate or polyethylene naphthalate, a polyimide film, a polyamideimide film, a polypropylene film, a polystyrene film, or other thermoplastic resin film. Among these, polyester films are preferred from the viewpoints of heat resistance, mechanical strength, handling, etc. A laminate of these films can also be used as the substrate.
[0017] From the viewpoint of improving mechanical strength, the above-mentioned thermoplastic resin film is preferably a film stretched in a uniaxial or biaxial direction.
[0018] The surface of the substrate on which the resin layer is provided may be subjected to a release treatment so that the resin layer can be easily peeled off from the substrate when the dry film is used. For example, a coating liquid prepared by dissolving or dispersing a release agent such as wax, silicone wax, or silicone resin in a suitable solvent is applied to the substrate surface by a known means such as a coating method such as a roll coating method or a spray coating method, a gravure printing method, or a screen printing method, and then dried, thereby performing the release treatment.
[0019] The thickness of the substrate is not particularly limited, but is appropriately selected from the range of about 10 to 150 μm depending on the application.
[0020] <Resin layer> The resin layer releasably provided on the above-mentioned substrate will be described. The resin layer contains polyimide and an epoxy compound as essential components. The dry film of the present invention is a coating film obtained by coating a substrate with a resin composition containing polyimide and an epoxy compound and drying the coating film as described below. Considering the practical use of the dry film, the coating film must be dried to the extent that the coating film is not sticky, that is, to the extent that the tack is eliminated. However, the dried coating film (i.e., the resin layer) has almost no tack, and when the dry film is attached (laminated) to a glass substrate, the adhesion between the resin layer and the glass substrate, which is the adherend, is poor. In particular, fluorinated polyimide is known as a highly transparent polyimide that is preferably used for optical applications such as display elements, but when the fluorinated polyimide is made into a dry film, the adhesion to the adherend is significantly reduced. In the present invention, by using a polyimide with a fluorine content of a certain value or less and using a specific epoxy compound in combination, the adhesion to the glass substrate, which is the adherend, can be improved even when the dry film is made into a dry film. Hereinafter, the components constituting the resin composition according to the present invention will be described.
[0021] <Polyimide> Polyimide has a structure represented by the following formula (1) in which polyamic acid, which is a reaction product of carboxylic anhydride and diamine, is imidized. The constitutional unit represented by formula (1) is a constitutional unit formed by the reaction of a tetracarboxylic acid compound and a diamine compound.
[0022] [ka]
[0023] In the above formula (1), X's each independently represent a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms, more preferably a divalent organic group having a cyclic structure having 4 to 40 carbon atoms. Examples of the cyclic structure include an alicyclic, aromatic, and heterocyclic structure. The organic group may have a hydrogen atom substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group, in which case the number of carbon atoms in the hydrocarbon group and the fluorine-substituted hydrocarbon group is preferably 1 to 8. However, even when fluorine is substituted, the fluorine content of the polyimide must be 25 mass% or less. When the fluorine content increases, the optical properties (light transmittance, YI value, haze) of the polyimide improve, but the adhesion to the glass substrate cannot be maintained. In an embodiment of the present invention, the polyimide may contain a plurality of types of X, and the plurality of types of X may be the same or different from each other. Examples of X include groups represented by the following formulas, in which the hydrogen atom in each group is substituted with a methyl group, a fluoro group, a chloro group or a trifluoromethyl group, and chain hydrocarbon groups having 6 or less carbon atoms.
[0024] [ka]
[0025] In the above formula, * represents a bond, A 1 , A 2 , A 3 are each independently a single bond, -O-, -S-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -SO2-, -CO-, or N(Q)-, where Q is a monovalent hydrocarbon group having 1 to 12 carbon atoms which may be substituted with a halogen atom. As an example, A 1 and A 3 is a single bond, -O- or -S-, and A 2 is -CH2-, -C(CH3)2-, -C(CF3)2- or SO2-. 1 and A 2The bonding positions of each ring and A 2 and A 3 The bonding positions of each of the rings are, independently of each other, preferably the meta or para positions, more preferably the para positions, relative to each ring.
[0026] Among the above groups, from the viewpoint of the surface hardness and bending resistance of the laminate, a group represented by the following formula: [ka] A group represented by the following formula is more preferred. Also, A 1 , A 2 and A 3 are preferably, independently of one another, a single bond, -O- or S-, and more preferably a single bond or O-, from the viewpoint of easily increasing the surface hardness and flexibility of the laminate.
[0027] In a preferred embodiment of the present invention, at least a portion of the multiple Xs in the above formula (1) are constitutional units represented by formula (2). [ka]
[0028] In formula (2), * represents a bond, R 1 ~R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms; R 1 ~R 8 The hydrogen atoms contained in may be, independently of one another, substituted with a halogen atom.
[0029] R 1 ~R 8 are each independently preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, wherein R 1 ~R 8The hydrogen atoms contained in R may be substituted, independently of one another, with a halogen atom. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. 1 ~R 8 are each independently more preferably a hydrogen atom, a methyl group, a fluoro group, a chloro group, or a trifluoromethyl group, from the viewpoint of the surface hardness, transparency, and bending resistance of the laminate, and particularly preferably R 1 , R 3 , R 4 , R 5 , R 6 , R 8 is a hydrogen atom, R 2 and R 7 is a hydrogen atom, a methyl group, a fluoro group, a chloro group, or a trifluoromethyl group, and particularly preferably R 2 and R 7 is a methyl group or a trifluoromethyl group. However, the fluorine content of the entire polyimide must be 25 mass % or less.
[0030] In a preferred embodiment of the present invention, the structural unit represented by the formula (2) is a structural unit represented by the formula (3). That is, at least a part of the multiple X's is a structural unit represented by the formula (3). In this case, the fluorine-containing skeleton increases the solubility of the polyimide in a solvent, and the storage stability of the polyimide-containing varnish is easily improved, and the viscosity of the varnish is easily reduced, and the coatability when forming a dry film is easily improved. In addition, the fluorine-containing skeleton improves the optical properties of the polyimide (total light transmittance, YI value, haze, etc.). However, from the viewpoint of adhesion to a glass substrate, the fluorine content of the entire polyimide needs to be 25 mass% or less. [ka]
[0031] In one embodiment of the present invention, X in the polyimide is preferably 30 mol % or more, more preferably 50 mol % or more, and even more preferably 70 mol % or more, represented by formula (2), particularly formula (3). When X in the polyimide is represented by formula (2), particularly formula (3), within the above range, the solubility in a solvent is easily improved by the skeleton containing elemental fluorine, and the storage stability of a varnish containing the polyimide is easily improved, and the viscosity of the varnish is easily reduced, improving the coatability. In addition, the skeleton containing elemental fluorine also improves optical properties such as total light transmittance, YI value, and haze. The proportion of the structural unit represented by formula (2) or (3) of X in the polyimide can be, for example, 1 It can be measured using H-NMR, but it can also be calculated from the ratio of the raw materials used.
[0032] In the above formula (1), Y represents a tetravalent organic group, preferably a tetravalent organic group having 4 to 40 carbon atoms, more preferably a tetravalent organic group having 4 to 40 carbon atoms and a cyclic structure. Examples of the cyclic structure include an alicyclic ring, an aromatic ring, and a heterocyclic structure. The organic group is an organic group in which a hydrogen atom in the organic group may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group, and in this case, the number of carbon atoms in the hydrocarbon group and the fluorine-substituted hydrocarbon group is preferably 1 to 8.
[0033] In one embodiment of the present invention, the polyimide may contain multiple types of Y, which may be the same or different from one another. Y is preferably a group represented by the following formula. Examples of these exemplified groups include groups in which a hydrogen atom is substituted with a methyl group, a fluoro group, a chloro group, or a trifluoromethyl group; and tetravalent chain hydrocarbon groups having 6 or less carbon atoms.
[0034] [ka]
[0035] In the above formula, * represents a bond, B 1represents a single bond, -O-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -Ar-, -SO2-, -CO-, -O-Ar-O-, -Ar-O-Ar-, -Ar-CH2-Ar-, -Ar-C(CH3)2-Ar-, or Ar-SO2-Ar-. Ar represents an arylene group having 6 to 20 carbon atoms in which a hydrogen atom may be substituted with a fluorine atom, and a specific example thereof is a phenylene group.
[0036] Among the above groups, from the viewpoint of the surface hardness and flex resistance of the laminate, groups represented by the following formulas are preferred. From the viewpoint of easily increasing the surface hardness and flex resistance of the laminate and easily reducing yellowness, each of the groups is preferably a single bond, -O-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2- or C(CF3)2-, more preferably a single bond, -O-, -CH2-, -CH(CH3)-, -C(CH3)2- or C(CF3)2-, and more preferably a single bond, -C(CH 3 )2- or C(CF3)2- are more preferred. [ka]
[0037] In one embodiment of the present invention, at least a part of the Y's in formula (1) are structural units represented by the following formula (4). When at least a part of the Y's in formula (1) are groups represented by formula (4), the solubility of the polyimide in a solvent is increased, the viscosity of a varnish containing the polyimide is easily reduced, and the coatability is improved. In addition, the optical properties of the laminate are improved. [ka]
[0038] In formula (5), * represents a bond, R 9 ~R 16 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms; R 9 ~R 16The hydrogen atoms contained in may be independently substituted with a halogen atom. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. From the viewpoint of easily improving the surface hardness, bending resistance, and optical properties of the laminate, R 9 ~R 16 are each independently more preferably a hydrogen atom, a methyl group, a fluoro group, a chloro group or a trifluoromethyl group, and particularly preferably R 9 , R 10 , R 11 , R 14 , R 15 and R 16 is a hydrogen atom, R 12 and R 13 is a hydrogen atom, a methyl group, a fluoro group, a chloro group, or a trifluoromethyl group, and particularly preferably R 12 and R 13 is a methyl group or a trifluoromethyl group.
[0039] In one embodiment of the present invention, the structural unit represented by the above formula (4) is preferably a group represented by the following formula (5). The fluorine-containing skeleton increases the solubility of the polyimide in a solvent, and the storage stability of the polyimide-containing varnish is easily improved, while the viscosity of the varnish is easily reduced, improving the coatability. In addition, the fluorine-containing skeleton improves the optical properties of the laminate. [ka]
[0040] In one embodiment of the present invention, preferably 50 mol % or more, more preferably 60 mol % or more, and even more preferably 70 mol % or more of Y in the polyimide is represented by formula (4), particularly formula (5). When Y in the polyimide within the above range is represented by formula (4), particularly formula (5), the fluorine-containing skeleton increases the solubility of the polyimide in a solvent, and the viscosity of a varnish containing the resin is easily reduced, and the processability of the resin layer is easily improved. In addition, the fluorine-containing skeleton easily improves the optical properties of the laminate. Preferably, 100 mol % or less of Y in the polyimide is represented by formula (4), particularly formula (5). Y in the polyimide may be formula (4), particularly formula (5). The ratio of the structural unit represented by formula (4) in Y in the polyimide is, for example, 1 It can be measured using H-NMR, but it can also be calculated from the ratio of the raw materials used.
[0041] The above-mentioned polyimide can contain, in addition to the constitutional unit represented by formula (1), a constitutional unit represented by formula (30) and / or a constitutional unit represented by formula (31). [ka]
[0042] In formula (30), Y1 is a tetravalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. Y 1 Examples of the Y groups are the above-mentioned preferred groups for Y. In one embodiment of the present invention, the polyimide has a plurality of Y groups. 1 may include multiple types of Y 1 may be the same or different from each other.
[0043] In formula (31), Y 2 Y is a trivalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 2Examples of the Y include a group in which any one of the bonds of the above-mentioned preferred groups for Y is replaced with a hydrogen atom, and a trivalent chain hydrocarbon group having 6 or less carbon atoms. In one embodiment of the present invention, the polyimide has a plurality of Y 2 may include multiple types of Y 2 may be the same or different from each other.
[0044] In formula (30) and formula (31), X 1 and X 2 are each independently a divalent organic group, and preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 and X 2 Examples of the group include the preferred groups for X mentioned above.
[0045] In one embodiment of the present invention, the polyimide comprises a constitutional unit represented by formula (1), and optionally a constitutional unit represented by formula (30) and / or formula (31). From the viewpoint of the optical properties, surface hardness and flex resistance of the laminate, the constitutional unit represented by formula (1) in the polyimide is preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more, based on all constitutional units represented by formula (1) and optionally formula (30) and formula (31). In the polyimide, the constitutional unit represented by formula (1) is usually 100% or less, based on all constitutional units represented by formula (1) and optionally formula (30) and / or formula (31). The above ratio can be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0046] In one embodiment of the present invention, from the viewpoint of adhesion between the resin layer and the glass substrate and the texture of the laminate, the polyimide may contain a structural unit represented by the following formula (40) in addition to the structural unit represented by formula (1) and, in some cases, the structural unit represented by formula (30) and / or formula (31). [ka]
[0047] In the above formula (40), * represents a bond, R 17 and R 18 are each independently a single bond, an alkylene group having 1 to 5 carbon atoms, or a divalent aromatic group having 6 or more carbon atoms; R 19 and R 20 are each independently an alkyl group having 1 to 5 carbon atoms, and R 21 and R 22 are each independently an aryl group having 4 to 10 carbon atoms; R 23 and R 24 At least one of these is an alkenyl group having 2 to 10 carbon atoms, and m1, m2 and m3 each independently is an integer of 1 or more.
[0048] The repeating unit having the structure of the above formula (40) contains all of a repeating unit substituted with an alkyl group, a siloxane repeating unit substituted with an aryl group, and a siloxane repeating unit substituted with an alkenyl group, thereby improving the tensile modulus of the resin layer and the adhesion between the resin layer and the glass substrate, and also improving the texture when formed into a laminate.
[0049] The order of the repeating units substituted with an alkyl group, the siloxane repeating units substituted with an aryl group, and the siloxane repeating units substituted with an alkenyl group can be changed as desired, and they may be positioned alternately.
[0050] In one embodiment of the present invention, in the structural unit represented by the above formula (40), R 17 and R 18 are each independently a single bond, an alkylene group having 1 to 5 carbon atoms, or a divalent aromatic group having 6 or more carbon atoms, and preferably an alkylene group having 3 or more carbon atoms. R3 and R4 are each independently an alkyl group having 1 to 5 carbon atoms, and preferably a methyl or ethyl group. Also, R 19 and R 20are each independently an aryl group having 4 to 10 carbon atoms, and preferably a phenyl group. Also, R 21 and R 22 At least one of them is an alkenyl group having 2 to 10 carbon atoms, and is preferably an ethenyl or propenyl group. The other one that is not an alkenyl group is an alkyl group having 1 to 5 carbon atoms.
[0051] In one embodiment of the present invention, in the structural unit represented by the above formula (40), m1, m2, and m3 are each independently an integer of 1 to 10. Specifically, m1 is an integer of 3 to 9, m2 is an integer of 2 to 9, and m3 is an integer of 1 to 5.
[0052] In one embodiment of the present invention, the structural unit represented by the above formula (40) is 5 mol % or more or 50 mol % or less, preferably 5 to 40 mol %, of all units from the viewpoint of the balance between heat resistance and adhesion.
[0053] The polyimide may contain halogen atoms such as fluorine atoms, which can be introduced, for example, by the above-mentioned fluorine-containing substituents, but the fluorine content of the polyimide must be 25 mass% or less. When the polyimide contains fluorine atoms, the optical properties (light transmittance, YI value, haze) of the resin layer are improved, but the adhesion to the glass substrate is reduced. The fluorine atom content in the polyimide is preferably 0 to 23 mass%, more preferably 0 to 20 mass%.
[0054] The imidization rate of the polyimide is preferably 90% or more, more preferably 93% or more, and even more preferably 96% or more. From the viewpoint of easily increasing the optical homogeneity of the laminate, it is preferable that the imidization rate is equal to or higher than the above lower limit. The upper limit of the imidization rate is 100% or less. The imidization rate indicates the ratio of the molar amount of imide bonds in the polyimide to twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide. In addition, when the polyimide contains a tricarboxylic acid compound, it indicates the ratio of the molar amount of imide bonds in the polyimide to the sum of twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide and the molar amount of the constituent units derived from the tricarboxylic acid compound. The imidization rate can be determined by IR method, NMR method, etc.
[0055] Polyimide can be produced, for example, from a tetracarboxylic acid compound and a diamine compound as main raw materials. Note that a diisocyanate compound may be used instead of the diamine compound.
[0056] Examples of diamine compounds used in the production of polyimide include aliphatic diamines, aromatic diamines, diaminosiloxanes, and mixtures thereof. In this embodiment, the term "aromatic diamine" refers to a diamine in which an amino group is directly bonded to an aromatic ring, and may include an aliphatic group or other substituents in a part of its structure. The aromatic ring may be a single ring or a condensed ring, and examples thereof include a benzene ring, a naphthalene ring, an anthracene ring, and a fluorene ring, but are not limited thereto. Among these, the benzene ring is preferable. The term "aliphatic diamine" refers to a diamine in which an amino group is directly bonded to an aliphatic group, and may include an aromatic ring or other substituents in a part of its structure. Furthermore, the term "diaminosiloxane" refers to a compound having an amino group at the end of a siloxane skeleton, and may include a part of its structure substituted by a hydrocarbon group.
[0057] Examples of the aliphatic diamine include acyclic aliphatic diamines such as hexamethylenediamine, and cyclic aliphatic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine, and 4,4'-diaminodicyclohexylmethane. These can be used alone or in combination of two or more.
[0058] Examples of aromatic diamines include aromatic diamines having one aromatic ring, such as p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-xylylenediamine, p-xylylenediamine, 1,5-diaminonaphthalene, and 2,6-diaminonaphthalene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, and 3,3'-diaminodiphenyl sulfone (sometimes abbreviated as 3,3'DDS), 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (sometimes abbreviated as TPE-R), and 1,3-bis(3-aminophenoxy)benzene. Examples of aromatic diamines having two or more aromatic rings include aromatic diamines having two or more aromatic rings, such as 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, and 9,9-bis(4-amino-3-fluorophenyl)fluorene. These can be used alone or in combination of two or more.
[0059] The aromatic diamine is preferably 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone (3,3'DDS), 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene, These are 4,4'-bis(4-aminophenoxy)biphenyl (APB-N), bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl (TFMB), and 4,4'-bis(4-aminophenoxy)biphenyl. These can be used alone or in combination of two or more.
[0060] Examples of diaminosiloxanes include 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(4-aminobutyl)tetramethyldisiloxane, α,ω-bis(2-aminoethyl)polydimethylsiloxane, α,ω-bis(3-aminopropyl)polydimethylsiloxane, α,ω-bis(4-aminobutyl)polydimethylsiloxane, α,ω-bis(5-aminopentyl)polydimethylsiloxane, α,ω-bis[3-(2-aminophenyl)propyl]polydimethylsiloxane, and α,ω-bis[3-(4-aminophenyl)propyl]polydimethylsiloxane. These can be used alone or in combination of two or more.
[0061] Among the above diamine compounds, from the viewpoints of surface hardness, flexibility, and coloring degree (YI value) of the laminate, it is preferable to use one or more selected from the group consisting of aromatic diamines having a biphenyl structure, and among these, it is more preferable to use one or more selected from the group consisting of 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-bis(4-aminophenoxy)biphenyl, and 4,4'-diaminodiphenyl ether, and it is even more preferable to use 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl (TFMB).
[0062] From the viewpoint of flexibility of the laminate, it is preferable to use one or more selected from the group consisting of aromatic diamines having an ether bond, and among these, it is more preferable to use one or more selected from the group consisting of 4,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), and 1,3-bis(3-aminophenoxy)benzene (APB-N), and it is even more preferable to use 1,3-bis(4-aminophenoxy)benzene (TPE-R), and 1,3-bis(3-aminophenoxy)benzene (APB-N).
[0063] From the viewpoint of the transparency of the laminate, it is preferable to use one or more selected from the group consisting of aromatic diamines having a sulfone bond, and among these, it is more preferable to use one or more selected from the group consisting of 3,3'-diaminodiphenyl sulfone (3,3'DDS) and bis[4-(4-aminophenoxy)phenyl]sulfone, and it is even more preferable to use 3,3'-diaminodiphenyl sulfone (3,3'DDS).
[0064] The tetracarboxylic acid compound used in the production of polyimide includes aromatic tetracarboxylic acid compounds such as aromatic tetracarboxylic acid dianhydrides, and aliphatic tetracarboxylic acid compounds such as aliphatic tetracarboxylic acid dianhydrides. The tetracarboxylic acid compounds may be used alone or in combination of two or more. The tetracarboxylic acid compounds may be dianhydrides or tetracarboxylic acid compound analogues such as acid chloride compounds.
[0065] Specific examples of aromatic tetracarboxylic dianhydrides include non-condensed polycyclic aromatic tetracarboxylic dianhydrides, monocyclic aromatic tetracarboxylic dianhydrides, and condensed polycyclic aromatic tetracarboxylic dianhydrides. Examples of non-condensed polycyclic aromatic tetracarboxylic dianhydrides include 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, and 2,2-bis[4-(3,4-dicarboxyphenoxyphenyl)]propane dianhydride. (sometimes abbreviated as BisDA), 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (sometimes abbreviated as 6FDA), 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride. Furthermore, an example of the monocyclic aromatic tetracarboxylic dianhydride is 1,2,4,5-benzenetetracarboxylic dianhydride, and an example of the condensed polycyclic aromatic tetracarboxylic dianhydride is 2,3,6,7-naphthalenetetracarboxylic dianhydride.
[0066] Among the above, preferred are 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxyphenyl)]propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA), 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, and 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride. Examples of the dianhydride include 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride, and more preferably, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (6FDA), bis(3,4-dicarboxyphenyl)methane dianhydride, and 4,4'-(p-phenylenedioxy)diphthalic dianhydride. These can be used alone or in combination of two or more.
[0067] Examples of the aliphatic tetracarboxylic dianhydride include cyclic or non-cyclic aliphatic tetracarboxylic dianhydrides. The cyclic aliphatic tetracarboxylic dianhydride is a tetracarboxylic dianhydride having an alicyclic hydrocarbon structure, and specific examples thereof include cycloalkane tetracarboxylic dianhydrides such as 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, and 1,2,3,4-cyclopentane tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyl tetracarboxylic dianhydride, and positional isomers thereof. These can be used alone or in combination of two or more. Specific examples of the non-cyclic aliphatic tetracarboxylic dianhydride include 1,2,3,4-butane tetracarboxylic dianhydride and 1,2,3,4-pentane tetracarboxylic dianhydride, and the like, and these can be used alone or in combination of two or more. Furthermore, a cyclic aliphatic tetracarboxylic acid dianhydride and a non-cyclic aliphatic tetracarboxylic acid dianhydride may be used in combination.
[0068] Among the above tetracarboxylic dianhydrides, from the viewpoints of high surface hardness, high transparency, high flexibility, high bending resistance, and low coloration of the laminate, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxyphenyl)]propane dianhydride, 3,3',4,4'-dicyclohexyl tetracarboxylic dianhydride, and mixtures thereof are preferred.
[0069] As the dicarboxylic acid compound used in the production of polyimide, terephthalic acid, 4,4'-oxybisbenzoic acid, or their acid chloride compounds are preferably used. In addition to terephthalic acid, 4,4'-oxybisbenzoic acid, or their acid chloride compounds, other dicarboxylic acid compounds may be used. Examples of other dicarboxylic acid compounds include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and their related acid chloride compounds, acid anhydrides, etc., and two or more of them may be used in combination. Specific examples include dicarboxylic acid compounds such as isophthalic acid, naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, and chain hydrocarbons having 8 or less carbon atoms, as well as compounds in which two benzoic acids are linked by a single bond, -CH2-, -C(CH3)2-, -SO2-, or a phenylene group, and acid chloride compounds thereof.Specific examples are preferably 4,4'-oxybis(benzoyl chloride) and terephthaloyl chloride, and more preferably a combination of 4,4'-oxybis(benzoyl chloride) and terephthaloyl chloride.
[0070] The polyimide may be a product obtained by further reacting tetracarboxylic acid and tricarboxylic acid, as well as their anhydrides and derivatives, in addition to the tetracarboxylic acid compound, as long as the various physical properties of the laminate are not impaired. Examples of the tetracarboxylic acid include water adducts of the anhydrides of the tetracarboxylic acid compounds. Examples of the tricarboxylic acid compound include aromatic tricarboxylic acids, aliphatic tricarboxylic acids, and their related acid chloride compounds and acid anhydrides, and two or more of these may be used in combination. Specific examples include anhydrides of 1,2,4-benzenetricarboxylic acid; 2,3,6-naphthalenetricarboxylic-2,3-anhydride; and compounds in which phthalic anhydride and benzoic acid are linked by a single bond, -O-, -CH2-, -C(CH3)2-, -SO2-, or a phenylene group.
[0071] In producing the polyimide, the amount of the diamine compound, tetracarboxylic acid compound and / or dicarboxylic acid compound used can be appropriately selected depending on the ratio of each of the desired structural units of the polyimide.
[0072] In the production of polyimide, the reaction temperature of the diamine compound, the tetracarboxylic acid compound and the dicarboxylic acid compound is not particularly limited, but is, for example, 5 to 350°C, preferably 20 to 200°C, and more preferably 25 to 100°C. The reaction time is also not particularly limited, but is, for example, about 30 minutes to 10 hours. If necessary, the reaction may be carried out under an inert atmosphere or reduced pressure. In a preferred embodiment, the reaction is carried out under normal pressure and / or an inert gas atmosphere with stirring. In addition, the reaction is preferably carried out in a solvent inert to the reaction.
[0073] The solvent is not particularly limited as long as it does not affect the reaction, and examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, γ-valerolactone, propylene glycol methyl ether acetate, and ethyl lactate; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, Examples of the solvent include ketone solvents such as methyl isobutyl ketone and N-methyl-2-pyrrolidone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; amide solvents such as N,N-dimethylacetamide and N,N-dimethylformamide; sulfur-containing solvents such as dimethylsulfone, dimethylsulfoxide, and sulfolane; carbonate solvents such as ethylene carbonate and propylene carbonate; and combinations (mixed solvents) thereof. Among these, amide solvents can be preferably used from the viewpoint of solubility.
[0074] In the imidization step in the production of polyimide, imidization can be carried out in the presence of an imidization catalyst. Examples of the imidization catalyst include aliphatic amines such as tripropylamine, dibutylpropylamine, and ethyldibutylamine; alicyclic amines (monocyclic) such as N-ethylpiperidine, N-propylpiperidine, N-butylpyrrolidine, N-butylpiperidine, and N-propylhexahydroazepine; azabicyclo[2.2.1]heptane, azabicyclo[3.2.1]octane, azabicyclo[2.2.2]octane, and azabicyclo[3.2. 2] Alicyclic amines (polycyclic), such as nonane; and aromatic amines, such as pyridine, 2-methylpyridine (2-picoline), 3-methylpyridine (3-picoline), 4-methylpyridine (4-picoline), 2-ethylpyridine, 3-ethylpyridine, 4-ethylpyridine, 2,4-dimethylpyridine, 2,4,6-trimethylpyridine, 3,4-cyclopentenopyridine, 5,6,7,8-tetrahydroisoquinoline, and isoquinoline.
[0075] In addition, from the viewpoint of facilitating the imidization reaction, it is preferable to use an acid anhydride together with the imidization catalyst. Examples of the acid anhydride include conventional acid anhydrides used in imidization reactions, and specific examples thereof include aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, and butyric anhydride, and aromatic acid anhydrides such as phthalic acid.
[0076] The polyimide may be isolated (separated and purified) by a conventional method, for example, a separation means such as filtration, concentration, extraction, crystallization, recrystallization, column chromatography, or a combination of these. In a preferred embodiment, the polyimide can be isolated by adding a large amount of alcohol such as methanol to a reaction solution containing a transparent polyamideimide resin to precipitate the resin, and then concentrating, filtering, drying, etc.
[0077] The weight average molecular weight (Mw) of the polyimide obtained as described above is preferably 30,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 500,000, from the viewpoints of solubility in a solvent when preparing a dry film and surface hardness and bending resistance of the resin layer when using the dry film for optical purposes. The weight average molecular weight (Mw) is a value measured by GPC (gel permeation chromatography) and calculated in terms of standard polystyrene.
[0078] The polyimide used in the present invention preferably has a YI value of 5.0 or less when it is made into a single layer film with a thickness of 50 μm. By using a polyimide with a small YI value, a laminate produced using the dry film can be more suitably used as a cover window of a display for a flexible device. The YI value is more preferably 2.0 or less. In this specification, the YI value (yellowness index) means a value calculated based on the formula YI=100×(1.2769X-1.0592Z) / Y by measuring the transmittance of light of 300 to 800 nm using an ultraviolet-visible-near infrared spectrophotometer in accordance with JIS K 7373:2006, determining the tristimulus values (X, Y, Z).
[0079] In addition, when the polyimide is made into a single layer film having a thickness of 50 μm, the haze of the single layer film is preferably 2.0 or less. By using a polyimide having a small haze in addition to the YI value, a laminate produced using the dry film can be more suitably used as a cover window for a display for a flexible device. It is more preferable that the haze is 1.0 or less. In this specification, the haze means a value measured by a known turbidity meter in accordance with JIS K 7136:2000.
[0080] <Epoxy compounds> The resin layer contains a specific epoxy compound in addition to the polyimide having a fluorine content of a certain value or less. The epoxy compound used in combination with the polyimide is an epoxy compound having an epoxy equivalent of 1000 g / eq or less and a molecular weight of 10,000 or less. By containing the specific epoxy compound in addition to the polyimide, the resin layer of the dry film can suppress the tack of the resin layer of the dry film at room temperature to improve the handling, while improving the adhesion to the adherend such as a glass substrate. The reason for this is not clear, but it is thought that the compatibility of the epoxy compound with the polyimide is good, and further, the epoxy compound reacts with a part of the amine or acid anhydride, which is the raw material of the polyimide, to show adhesion.
[0081] The epoxy equivalent means the total number of epoxy groups in an epoxy compound, and can be determined by the method described in JIS K7236.
[0082] As the epoxy compound that can be preferably used in the present invention, any epoxy compound having an epoxy equivalent of 1000 g / eq or less and a molecular weight of 10,000 or less can be used without particular limitation, and for example, biphenyl type, bisphenol A type, bisphenol F type, dicyclopentadiene type, naphthalene type, and epoxy compounds having a triazine ring can be preferably used. Specifically, bisphenols such as jER828, jER834, jER1001, and jER1004 manufactured by Mitsubishi Chemical Corporation, EPICLON840, EPICLON850, EPICRON860, and EPICLON1050 manufactured by DIC Corporation, Epotohto YD-011, YD-127, and YD-128 manufactured by Nippon Steel Sumitomo Chemical Co., Ltd., and AER330, AER331, AER661, and AER664 manufactured by Asahi Kasei Corporation (all trade names) can be used. Brominated epoxy resins such as EPICLON152 and EPICLON165 manufactured by DIC Corporation, Epototo YDB-400 and YDB-500 manufactured by Nippon Steel Sumitomo Chemical Co., Ltd., Sumi-Epoxy ESB-400 and ESB-700 manufactured by Sumitomo Chemical Co., Ltd.; jER152 and jER154 manufactured by Mitsubishi Chemical Corporation, EPICLONN-730, EPICLONN-770, and EPICLONN-865 manufactured by DIC Corporation; Novolac type epoxy resins such as YDCN-704 manufactured by Nippon Steel Sumitomo Chemical Co., Ltd., and EPPN-201, EOCN-1025, EOCN-1020, EOCN-104S, and NC-3000 manufactured by Nippon Kayaku Co., Ltd.; bisphenol F type epoxy resins such as EPICLON830 manufactured by DIC Corporation, jER807 manufactured by Mitsubishi Chemical Corporation, and Epotohto YDF-170 manufactured by Nippon Steel Sumitomo Chemical Co., Ltd. (all trade names); Hydrogenated bisphenol A type epoxy resins such as Epotohto ST-2004, ST-2007, and ST-3000 (trade names) manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd.; glycidyl amine type epoxy resins such as jER604 manufactured by Mitsubishi Chemical Corporation and Epotohto YH-434 (all trade names) manufactured by Nippon Steel Sumitomo Chemical Co., Ltd.; alicyclic epoxy resins such as Celloxide 2021P (trade name) manufactured by Daicel Corporation; YL-933 manufactured by Mitsubishi Chemical Corporation and TEN manufactured by The Dow Chemical Companytrihydroxyphenylmethane type epoxy resins such as EPPN-501, EPPN-502 (all trade names); bixylenol type or biphenol type epoxy resins or mixtures thereof such as YX-4000 (all trade names) manufactured by Mitsubishi Chemical Corporation; bisphenol S type epoxy resins such as EBPS-200 manufactured by Nippon Kayaku Co., Ltd. and EXA-1514 (trade name) manufactured by DIC Corporation; bisphenol A novolac type epoxy resins such as jER157S (trade name) manufactured by Mitsubishi Chemical Corporation; tetrahydroxyphenylmethane type epoxy resins such as jERYL-931 (trade name) manufactured by Mitsubishi Chemical Corporation. Phenylolethane type epoxy resins; heterocyclic epoxy resins such as TEPIC manufactured by Nissan Chemical Co., Ltd. (all trade names); tetraglycidyl xylenoylethane resins such as ZX-1063 manufactured by Nippon Steel Sumitomo Chemical Co., Ltd.; naphthalene group-containing epoxy resins such as ESN-190 and ESN-360 manufactured by Nippon Steel Chemical Co., Ltd. and HP-4032D and EXA-4710 manufactured by DIC Corporation; epoxy resins having a dicyclopentadiene skeleton such as HP-7200 and HP-7200H manufactured by DIC Corporation and XD-1000 manufactured by Nippon Kayaku Co., Ltd., but of course they are not limited to these. These epoxy resins can be used alone or in combination of two or more.
[0083] Among the above-mentioned epoxy compounds, those having a softening point of 150° C. or less can be preferably used. As described later, when a laminate is produced using the dry film of the present invention, after forming a resin layer on a glass substrate, it is preferable to heat the resin layer at a predetermined temperature in order to improve the adhesion between the glass substrate and the resin layer, and the heating temperature at this time is preferably equal to or higher than the softening point temperature of the epoxy compound. Therefore, if the softening point temperature of the epoxy compound is too high, the components in the resin layer may be thermally deteriorated during the production of the laminate.
[0084] From the viewpoints of transparency of the resin layer and adhesion to the adherend, the amount of the epoxy compound is preferably 1 to 50 mass %, and more preferably 3 to 40 mass %, of the non-volatile components in the resin composition for forming the resin layer.
[0085] <Solvent> The resin composition preferably contains a solvent in consideration of the formability of the resin layer. The solvent may be any solvent capable of dissolving the polyimide and the epoxy compound, but from the viewpoints of the coatability of the varnish and the transparency of the resulting resin layer, a solvent containing at least one selected from the group consisting of an ester group, an ether group, a ketone group, a hydroxyl group, a sulfone group, and a sulfinyl group is preferred.
[0086] Examples of the solvent having an ester group include ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, and dimethyl carbonate. Examples of solvents having a cyclic ester group include lactone solvents such as γ-butyrolactone (GBL), δ-valerolactone, ε-caprolactone, γ-crotonolactone, γ-hexanolactone, α-methyl-γ-butyrolactone, γ-valerolactone, α-acetyl-γ-butyrolactone, and δ-hexanolactone. Examples of the solvent having an ether group include tetrahydrofuran, dioxane, and dibutyl ether. Examples of the solvent having a ketone group include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Examples of the solvent having a hydroxyl group include phenol-based solvents such as m-cresol. Examples of the solvent having a sulfone group include methyl sulfone, ethyl phenyl sulfone, diethyl sulfone, diphenyl sulfone, sulfolane, bisphenol S, sorapsone, dapsone, bisphenol A polysulfone, and sulfolane. Solvents having a sulfinyl group include sulfoxide solvents such as N,N-dimethylsulfoxide (DMSO). In addition to the solvents listed above, amide solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc) can be used.
[0087] <Other ingredients> The resin composition may contain any component other than those described above, such as a leveling agent for improving the coatability of the varnish when producing a dry film, a dispersant, a surfactant, a retardation regulator, an antioxidant, an ultraviolet inhibitor, a light stabilizer, a plasticizer, waxes, fillers, pigments, dyes, foaming agents, defoamers, dehydrating agents, antistatic agents, antibacterial agents, antifungal agents, etc. Among the above-mentioned colorants, the resin composition of the present invention preferably contains a bluing agent for improving the yellowish color derived from the polyimide.
[0088] The bluing agent is an additive (dye, pigment) that absorbs light in a wavelength range, for example, from orange to yellow, in the visible light range and adjusts the hue. Examples of the bluing agent include inorganic dyes and pigments such as ultramarine, Prussian blue, and cobalt blue, and organic dyes and pigments such as phthalocyanine bluing agents and condensed polycyclic bluing agents. The bluing agent is not particularly limited, but from the viewpoints of heat resistance, light resistance, and solubility, condensed polycyclic bluing agents are preferred, and anthraquinone bluing agents are more preferred. The bluing agent may be used alone or in combination of two or more types.
[0089] Examples of the condensed polycyclic bluing agent include anthraquinone bluing agents, indigo bluing agents, and phthalocyanine bluing agents. Among these, it is preferable to contain an anthraquinone bluing agent from the viewpoints of heat resistance, light resistance, and solubility.
[0090] From the viewpoint of maintaining a high total light transmittance of the resin layer formed from the resin composition, it is preferable to relatively reduce the total amount (mixture amount) of the bluing agent, and it is also preferable to use a small number of types of bluing agents. From the viewpoint of maintaining the total light transmittance while reducing the YI value, the content of the bluing agent is preferably 5 to 100 ppm, more preferably 10 to 70 ppm, based on the solid content of the resin composition.
[0091] <Resin layer> The resin layer can be formed by dissolving or dispersing the above-mentioned polyimide, epoxy compound, and any other component as required in a solvent to prepare a varnish, applying the varnish to a substrate to form a coating film, and then drying the coating film to remove the solvent. The coating process can be performed using various coating devices, and known coating methods such as spin coating, slit coating, slot die coating, and blade coating may be used.
[0092] The drying step of the coating film is not particularly limited as long as the temperature is such that the solvent volatilizes, but from the viewpoint of obtaining a resin layer with high transparency, the drying step is preferably carried out at 60 to 140° C. for about 30 seconds to 30 minutes.
[0093] The thickness of the resin layer can be adjusted by the amount of varnish applied to the substrate, but in the present invention, from the viewpoint of achieving both adhesion to the glass substrate and surface hardness when formed into a laminate, the thickness is preferably 5 to 25 μm, more preferably 10 to 20 μm. The total thickness of the glass substrate and the resin layer is preferably 30 to 135 μm, more preferably 30 to 100 μm.
[0094] In addition, when the resin layer is a single layer film having a thickness of 50 μm, the single layer film preferably has a total light transmittance of 88% or more. The total light transmittance of 88% or more allows the laminate to be suitably used as a cover window for a display for a flexible device. The total light transmittance is more preferably 90% or more. In this specification, the total light transmittance means a value measured by a known turbidimeter in accordance with JIS K 7375:2008.
[0095] <Protective film> In the dry film of the present invention, a protective film 30 may be further provided on the side of the resin layer 20 opposite to the side in contact with the substrate 10, as shown in FIG. 2, for the purpose of preventing adhesion of dust and the like to the surface of the resin layer and improving handleability.
[0096] As the protective film, for example, a polyester film, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a surface-treated paper, etc. can be used, but it is preferable to select a material such that the adhesive strength between the protective film and the resin layer is smaller than the adhesive strength between the substrate and the resin layer. In addition, in order to make it easier to peel off the protective film when using the dry film, the surface of the protective film that contacts the resin layer may be subjected to the above-mentioned release treatment.
[0097] The thickness of the protective film is not particularly limited, but is appropriately selected depending on the application within the range of about 10 to 150 μm.
[0098] [Laminate] The laminate according to the present invention will be described with reference to the drawings. FIGS. 3 to 5 are schematic cross-sectional views showing an embodiment of the laminate according to the present invention. As shown in FIG. 3, the laminate 2 according to the present invention includes a glass substrate 40 and a resin layer 20 provided on one of the main surfaces 40A of the glass substrate 40. According to an embodiment of the laminate according to the present invention, the laminate 2 may include a functional layer 50 on the outermost surface 20A of the resin layer as shown in FIG. 4. According to an embodiment of the laminate according to the present invention, the laminate 2 may include a support 60 on the other main surface 40B side of the glass substrate as shown in FIG. 5. Although not shown, in the embodiment shown in FIG. 5, the glass substrate 40 and the support 60 may be laminated via an adhesive. Hereinafter, each layer constituting the laminate according to the present invention will be described in detail.
[0099] <Glass substrate> The glass substrate constituting the laminate of the present invention has a thickness of 25 to 100 μm. A glass substrate having a thickness of 25 to 100 μm can be used to form a laminate having bending resistance and impact resistance. The thickness of the glass substrate is preferably 30 to 70 μm from the viewpoint of achieving both manufacturing cost and bending resistance and impact resistance.
[0100] The glass substrate can be used without any particular limitation as long as it has the above thickness, but silicate glass or silica glass is preferable, and more preferably borosilicate glass, soda-lime glass, or aluminosilicate glass. Particularly preferable is chemically strengthened glass or alkali-free glass of these glasses. The chemically strengthened glass is a glass material obtained by chemically strengthening the above glass material. The chemical strengthening treatment can be performed by a conventionally known method. For example, by immersing the glass substrate in a melt of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius, the metal ion with a small ionic radius (typically Na ion or Li ion) in the glass substrate is replaced with a metal ion with a large ionic radius, and as a result, a residual compressive stress can be generated on the surface of the glass substrate. The chemically strengthened glass is superior in compressive strength, bending strength, and impact resistance compared to non-chemically strengthened glass. Moreover, the alkali-free glass is glass that does not substantially contain an alkali component (alkali metal oxide), and specifically, it refers to glass with a weight ratio of the alkali component of 3000 ppm or less. The weight ratio of the alkaline component is preferably 1000 ppm or less, more preferably 500 ppm or less, and most preferably 300 ppm or less.
[0101] The flexural modulus of the glass substrate is preferably 50 to 150 GPa, and more preferably 70 to 100 GPa. In this specification, the flexural modulus refers to a value measured at 25° C. in accordance with JIS R 1602:1995.
[0102] The above-mentioned glass substrate may be a commercially available one, and examples thereof include Dragontrail (registered trademark) (manufactured by AGC Corporation: material = aluminosilicate, containing silicon, thickness = 70 μm), SCHOTT AS 87 eco (manufactured by SCHOTT: material = aluminosilicate, thickness = 25 μm, 50 μm, 70 μm), SCHOTT Xensation (registered trademark) Up (manufactured by SCHOTT: material = aluminosilicate, thickness = 30 μm, 50 μm, 70 μm), D263 (registered trademark) Teco (manufactured by SCHOTT: material = borosilicate, thickness = 30 μm, 70 μm), and G-Leaf (registered trademark) manufactured by Nippon Electric Glass Co., Ltd.: material = alkali-free glass, thickness = 50 μm, 100 μm).
[0103] <Resin layer> The resin layer can be formed by using the above-mentioned dry film. Hereinafter, a method for forming a resin layer using the dry film of the present invention will be described. First, the dry film is attached to one of the main surfaces of the glass substrate so as to contact the resin layer of the dry film. If the dry film has a protective film, the protective film is peeled off from the dry film to expose the surface of the resin layer, and then the dry film is attached to the glass substrate.
[0104] The glass substrate and the dry film are preferably laminated under pressure and heat using a vacuum laminator or the like. By using such a vacuum laminator, the resin layer of the dry film and the glass substrate can be closely attached to each other without air bubbles being mixed between them. The pressure condition is preferably about 0.1 to 2.0 MPa, and the heating condition is preferably 40 to 120°C.
[0105] After the dry film is laminated to the glass substrate, the substrate is peeled off from the dry film to form a resin layer on the glass substrate. The resin layer is then heated to a temperature equal to or higher than the softening point of the epoxy compound, thereby improving the adhesion between the resin layer and the glass substrate.
[0106] <Functional layer> The functional layer that is provided on the resin layer as desired will be described. The function of the functional layer is not particularly limited, and may be a general function adopted for the cover window of a flexible display element, such as a hard coat function, an antistatic function, an antiglare function, a low reflection function, an antireflection function, an antifouling function, a gas barrier function, a primer function, an electromagnetic wave shielding function, an undercoat function, an ultraviolet absorbing function, an adhesive function, and a hue adjusting function. The functional layer may be a layer having one type of function, or a layer having two or more types of functions. From the viewpoint of easy use as a cover window, at least one of the functional layers is preferably a layer having at least one function selected from the group consisting of a hard coat function, an antistatic function, an antiglare function, a low reflection function, an antireflection function, and an antifouling function. The functional layer may have multiple functions in one layer, or two or more layers having each function may be laminated. When two or more layers are laminated, the order of lamination is appropriately set according to the function.
[0107] The thickness of the functional layer may be appropriately set depending on the intended function, but from the viewpoint of making the laminate lighter and improving its optical homogeneity, it is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less.
[0108] (Hard coat function) The hard coat function is a function of protecting the optical film by imparting scratch resistance, chemical resistance, etc. to the surface of the optical film. In the optical laminate of the present invention, the functional layer may be a layer having a hard coat function (hard coat layer). As the hard coat layer, a known one may be appropriately adopted, and examples thereof include known hard coat layers such as acrylic, epoxy, urethane, benzyl chloride, and vinyl. Among these, from the viewpoint of suppressing the decrease in visibility in the wide angle direction of the optical laminate and improving the bending resistance, acrylic, urethane, and combinations thereof are preferred. For example, the hard coat layer may be a cured product of a composition containing an active energy ray curable compound. The active energy ray curable compound is a compound having the property of being cured by irradiation with active energy rays such as electron beams and ultraviolet rays. Examples of such active energy ray curable compounds include electron beam curable compounds that are cured by irradiation with electron beams and ultraviolet ray curable compounds that are cured by irradiation with ultraviolet rays. These compounds are compounds similar to the main components of hard coat agents used in the formation of ordinary hard coat layers, and examples thereof include (meth)acrylic resins. In particular, among (meth)acrylic resins, those containing a polyfunctional (meth)acrylate compound as a main component are preferred. In this specification, (meth)acrylic means acrylic and / or methacrylic, and (meth)acrylate means acrylate and / or methacrylate.
[0109] The polyfunctional (meth)acrylate compound is a compound having at least two acryloyloxy groups and / or methacryloyloxy groups in the molecule, and specifically includes ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerin tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tris((meth)acryloyloxyethyl)isocyanurate, a phosphazene-based acrylate compound or a phosphazene-based methacrylate compound in which a (meth)acryloyloxy group has been introduced into the phosphazene ring of a phosphazene compound, a urethane (meth)acrylate compound obtained by reacting a polyisocyanate having at least two isocyanate groups in the molecule with a polyol compound having at least one (meth)acryloyloxy group and a hydroxyl group, a polyester (meth)acrylate compound obtained by reacting a polyol compound having at least two carboxylic acid halides in the molecule with at least one (meth)acryloyloxy group and a hydroxyl group, and oligomers such as dimers and trimers of the above-mentioned compounds.
[0110] These compounds may be used alone or in a mixture of two or more kinds. In addition to the above-mentioned polyfunctional (meth)acrylate compounds, at least one monofunctional (meth)acrylate may be used. Examples of monofunctional (meth)acrylates include hydroxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and glycidyl (meth)acrylate. These compounds may be used alone or in a mixture of two or more kinds. The content of the monofunctional (meth)acrylate compound is preferably 10% by mass or less based on the solid content of the compound contained in the composition for forming the functional layer (paint for the hard coat layer). In this specification, the solid content means all components except the solvent contained in the curable composition.
[0111] A polymerizable oligomer may be added to the functional layer, for example, for the purpose of adjusting hardness. Examples of such oligomers include macromonomers such as (meth)acrylate-terminated polymethyl methacrylate, styryl-terminated poly(meth)acrylate, (meth)acrylate-terminated polystyrene, (meth)acrylate-terminated polyethylene glycol, (meth)acrylate-terminated acrylonitrile-styrene copolymer, and (meth)acrylate-terminated styrene-methyl (meth)acrylate copolymer. When a polymerizable oligomer is added, the content thereof is preferably 5 to 50 mass % based on the solid content of the functional layer-forming composition.
[0112] The active energy ray curable compound may be used in the form of a solution mixed with a solvent. The active energy ray curable compound or its solution may be commercially available as a hard coat agent. Specific examples of commercially available hard coat agents include NK Hard M101 (urethane acrylate compound, Shin-Nakamura Chemical Co., Ltd.), NK Ester A-TMM-3L (tetramethylolmethane triacrylate, Shin-Nakamura Chemical Co., Ltd.), NK Ester A-9530 (dipentaerythritol hexaacrylate, Shin-Nakamura Chemical Co., Ltd.), KAYARAD (registered trademark) DPCA series (derivatives of dipentaerythritol hexaacrylate compound, Nippon Kayaku Co., Ltd.), Aronix (registered trademark) M-8560 (polyester acrylate compound, Toa Gosei Co., Ltd.), New Frontier (registered trademark) TEICA (tris(acryloyloxyethyl) isocyanurate, Daiichi Kogyo Seiyaku Co., Ltd.), and PPZ (phosphazene-based methacrylate compound, Kyoeisha Chemical Co., Ltd.).
[0113] When ultraviolet rays or visible light are used as the active energy rays, a photopolymerization initiator is usually used as the polymerization initiator. Examples of the photopolymerization initiator include acetophenone, acetophenone benzyl ketal, anthraquinone, 1-(4-isopropylphenyl-2-hydroxy-2-methylpropan-1-one, carbazole, xanthone, 4-chlorobenzophenone, 4,4'-diaminobenzophenone, 1,1-dimethoxydeoxybenzoin, 3,3'-dimethyl-4-methoxybenzophenone, thioxanthone, 2,2-dimethoxy-2-phenylacetophenone, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, triphenylamine, 2 ,4,6-trimethylbenzoyldiphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, fluorenone, fluorene, benzaldehyde, benzoin ethyl ether, benzisopropyl ether, benzophenone, Michler's ketone, 3-methylacetophenone, 3,3',4,4'-tetratert-butylperoxycarbonylbenzophenone (BTTB), 2-(dimethylamino)-1-[4-(morpholinyl)phenyl]-2-phenylmethyl)-1-butanone, 4-benzoyl-4'-methyldiphenyl sulfide, benzyl, and the like.
[0114] The photopolymerization initiator may be used in combination with a dye sensitizer. Examples of the dye sensitizer include xanthene, thioxanthene, coumarin, and ketocoumarin. Examples of the combination of the photopolymerization initiator and the dye sensitizer include a combination of BTTB and xanthene, a combination of BTTB and thioxanthene, a combination of BTTB and coumarin, and a combination of BTTB and ketocoumarin.
[0115] When using a photopolymerization initiator, the amount of the photopolymerization initiator is preferably 0.1 parts by mass or more per 100 parts by mass of the active energy ray curable compound. When the amount of the photopolymerization initiator is within the above range, a sufficient curing speed tends to be obtained. The amount of the photopolymerization initiator is preferably 10 parts by mass or less per 100 parts by mass of the active energy ray curable compound.
[0116] The thickness of the hard coat layer can be appropriately set, but from the viewpoints of the bending resistance, surface hardness and optical uniformity of the laminate, it is preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less.
[0117] The method for forming a hard coat layer on the surface of a resin layer may be, for example, to apply a composition for forming a hard coat layer containing an active energy ray curable compound (active energy ray curable resin) to the surface of the resin layer and irradiate the active energy ray. Such a composition can be obtained by mixing the active energy ray curable compound with additives and the like as necessary. The cured product of the composition for forming a hard coat layer constitutes the hard coat layer.
[0118] The composition for forming a hard coat layer preferably contains a solvent, and in the composition for forming a hard coat layer, the active energy ray curable compound is preferably diluted with a solvent.In this case, the composition may be produced by mixing the active energy ray curable compound with various additives (e.g., silicone oil, etc.) for imparting surface smoothness, etc., and then diluting the mixture obtained with a solvent, or by diluting the active energy ray curable compound with a solvent and then mixing the additives, or by mixing the active energy ray curable compound with an additive previously diluted with a solvent, or by mixing the active energy ray curable compound previously diluted with a solvent and the additive previously diluted with a solvent.The composition after mixing may be further stirred.
[0119] From the viewpoint of facilitating application, it is preferable that the composition for forming a hard coat layer contains a suitable solvent. The solvent can be appropriately selected from aliphatic hydrocarbons such as hexane and octane, aromatic hydrocarbons such as toluene and xylene, alcohols such as ethanol, 1-propanol, isopropanol, and 1-butanol, ketones such as methyl ethyl ketone and methyl isobutyl ketone, esters such as ethyl acetate and butyl acetate, and cellosolves. These organic solvents may be mixed and used as necessary. From the viewpoint of easily evaporating the organic solvent by heating the composition for forming a hard coat layer after application, the boiling point of the solvent is preferably in the range of 70°C to 200°C. The type and amount of the solvent are appropriately selected depending on the type and amount of the active energy ray curable compound used, the material and shape of the resin layer, the application method, and the desired thickness of the hard coat layer.
[0120] (Anti-static function) The antistatic function is a function of preventing the surface of the laminate from being charged. In the laminate of the present invention, the functional layer may be a layer having an antistatic function (antistatic layer). As a method for forming an antistatic layer, in addition to the method of adding an antistatic agent to the composition for forming a hard coat layer to impart an antistatic function to the hard coat layer, a method of applying an antistatic layer forming composition obtained by diluting the antistatic agent with a solvent or the like onto the hard coat layer formed on the surface of the resin layer and drying it as necessary to form a single film can be mentioned. The antistatic agent may be contained as a structural unit having an antistatic function in a part of the resin constituting the functional layer (for example, the cured product of the above-mentioned active energy ray curable compound), or may be added as an additive to the resin forming the functional layer. When the antistatic agent is added as an additive, the amount of the antistatic agent added is preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.1 to 10% by mass based on the solid content of the composition for forming the functional layer.
[0121] (Anti-glare function) The antiglare function is a function of preventing reflection of external light by scattering and reflecting light. In the laminate of the present invention, the functional layer may be a layer having an antiglare function (antiglare layer). As the antiglare layer, a known material may be appropriately adopted. For example, the antiglare function may be imparted by forming a layer having a fine uneven shape on the surface using a resin composition containing one or more types of translucent fine particles in a translucent resin. More specifically, such an antiglare layer can be formed by, for example, applying a translucent resin solution in which translucent fine particles as a filler are dispersed on the surface of the resin layer, and adjusting the thickness of the application so that the translucent fine particles become the convex parts on the surface of the antiglare layer. In this specification, "translucency" means that light can be transmitted almost completely regardless of the presence or absence of scattering inside the substance.
[0122] (Anti-reflection and low-reflection functions) The anti-reflection function and the low-reflection function are functions to prevent or reduce the reflection of external light. In the laminate of the present invention, the functional layer may be a layer (anti-reflection layer) having a function to prevent the reflection of external light, or may be a layer (low-reflection layer) having a function to reduce the reflection of external light. The anti-reflection layer and the low-reflection layer may be a single layer or a multilayer.
[0123] The antireflection layer may include a low refractive index layer. The antireflection layer may also be a layer having a multilayer structure including a low refractive index layer and a high refractive index layer and / or a medium refractive index layer laminated between the low refractive index layer and the resin layer. The above-mentioned hard coat layer may be provided between the antireflection layer and the resin layer.
[0124] The thickness of the antireflection layer is preferably 0.01 to 1 μm, more preferably 0.02 to 0.5 μm. Examples of the antireflection layer include a low refractive index layer having a refractive index (e.g., a refractive index of 1.3 to 1.45) smaller than that of the resin layer or other functional layer on which the antireflection layer is provided, and a layer in which a low refractive index layer made of a thin film of an inorganic compound and a high refractive index layer made of a thin film of an inorganic compound are alternately laminated. Here, the refractive index of the high refractive index layer may be larger than that of the low refractive index layer, and is preferably 1.60 or more.
[0125] The material forming the low refractive index layer is not particularly limited as long as it has a low refractive index. For example, it may be a resin material such as an active energy ray curable resin (e.g., an ultraviolet curable acrylic resin), a hybrid material in which inorganic particles such as colloidal silica are dispersed in a resin, or a sol-gel material using a metal alkoxide such as tetraethoxysilane. These materials forming the low refractive index layer may be polymerized polymers or may be precursor monomers or oligomers. In addition, it is preferable that the material constituting the antireflection layer contains a compound containing fluorine, since it can impart an antifouling function to the antireflection layer.
[0126] The high refractive index layer can be formed by applying a coating liquid containing a cured product of the above-mentioned active energy ray curable resin or a light-transmitting resin such as a metal alkoxide polymer and inorganic fine particles and / or organic fine particles, and then curing the coating film as necessary. Examples of inorganic fine particles include zinc oxide, titanium oxide, cerium oxide, aluminum oxide, silane oxide, tantalum oxide, yttrium oxide, ytterbium oxide, zirconium oxide, antimony oxide, and indium tin oxide (ITO). The high refractive index layer containing these inorganic fine particles can also have an antistatic function.
[0127] The low-reflection layer is a layer formed of a low-refractive index material having a lower refractive index than the resin layer or other functional layers that are provided as desired. The low-refractive index layer can be formed by applying a coating liquid containing a cured product of the above-mentioned active energy ray-curable resin, a light-transmitting resin such as a metal alkoxide-based polymer, and inorganic fine particles, and then curing the coating film as necessary. Specific examples of such low-refractive index materials include inorganic low-refractive materials in which inorganic material fine particles such as lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), and cryolite (3NaF·AlF3 or Na3AlF6) are contained in acrylic resins or epoxy resins; and organic low-refractive materials such as fluorine-based or silicone-based organic compounds, thermoplastic resins, thermosetting resins, and ultraviolet-curable resins.
[0128] <Touch sensor function> A touch sensor function can be imparted to the laminate by forming a transparent electrode layer on the surface of the resin layer. For example, a transparent electrode layer can be formed on the surface of the resin layer or other functional layers that are provided as desired, using a sputtering device. This allows the laminate of the present invention to be used as a cover window to serve as a touch panel like a transparent electrode.
[0129] <Support> The laminate of the present invention can improve the mechanical strength of the laminate by providing a support on the surface of the glass substrate opposite to the surface on which the resin layer is formed. Any material having optical transparency, mechanical strength, and flexibility can be used without particular limitation, and for example, a transparent resin sheet such as polyimide, polyethylene terephthalate, polycarbonate, polyethersulfone, polyetheretherketone, polyvinyl fluoride, polyacrylate, polypropylene, polyethylene, amorphous polyolefin, or fluorine-based resin can be suitably used.
[0130] The thickness of the support may be appropriately determined depending on the application of the laminate. For example, when the laminate is used as a cover window of a flexible display element, the thickness is preferably 40 to 200 μm, more preferably 50 to 100 μm.
[0131] <Applications of laminates> A flexible display element can be manufactured using the laminate of the present invention. Flexible display elements include organic EL displays, such as bottom-emission type flexible organic EL displays and top-emission type flexible organic EL displays; or flexible liquid crystal displays. When the laminate of the present embodiment is used as a cover window for a flexible display element, the flexible display element is preferably equipped with a light source, and the light from the light source is preferably output to the outside of the flexible display element through the laminate of the present embodiment. When the laminate of the present embodiment is used as a cover window for a flexible display element, the laminate is disposed so that the glass substrate is disposed closer to the light source than the resin layer. EXAMPLES
[0132] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" and "%" are all based on mass unless otherwise specified.
[0133] <Preparation of polyimide> The following polyimides 1 to 6 were prepared. Polyimide 1: Into a 500 ml separable flask equipped with a nitrogen inlet tube and a stirrer, 2.0 g (0.007 mol) of 1,3-bis(3-aminophenoxy)benzene (APB-N), 3.3 g (0.01 mol) of 1,3-bis(4-aminophenoxy)benzene (TPE-R), 2.8 g (0.01 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (PAM-E), 15.9 g (0.03 mol) of 2,2-bis[4-(3,4-dicarboxyphenoxyphenyl)]propane dianhydride (BisDA), 56 g of ethyl benzoate, 0.47 g (0.006 mol) of pyridine, and 10 g of toluene were added, and the mixture was reacted for 4 hours at 180° C. under a nitrogen atmosphere while removing toluene from the system during the reaction, thereby obtaining a 30 wt % polyimide solution. To the obtained polyimide solution, 59.5 mL of DMAC and 59.5 mL of methanol were added and stirred until homogenized. The obtained solution was dropped into 300 mL of ion-exchanged water and re-precipitated to obtain solid polyimide 1. The weight average molecular weight (Mw) measured by gel permeation chromatography was 300,000, and the polydispersity expressed by weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.2. The fluorine content in the polyimide was 0%.
[0134] Polyimide 2: In a 200 mL glass vial, 60 g of the solvent N,N-dimethylacetamide (DMAC) and 3.8 g (0.012 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) were added and stirred to dissolve TFMB in DMAC. Next, while stirring the contents in the vial, 3.7 g (0.012 mol) of 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride (HBPDA) was added over about 5 minutes under a nitrogen stream, and the polymerization reaction was carried out by continuing to stir for 6 hours while adjusting the temperature to be in the range of 20 to 40 ° C., thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.00, and the concentration of the polyamic acid solution was 13.0 wt%. Next, 5.9 g of pyridine was added to the polyamic acid solution as an imidization accelerator, and the temperature was kept within a range of 30 to 40°C while stirring. 7.1 g (0.07 mol) of acetic anhydride was slowly added dropwise as an imidization agent over a period of about 10 minutes. The liquid temperature was then further kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. 59.5 mL of DMAC and 59.5 mL of methanol were added to the obtained polyimide solution containing the imidization agent and the imidization accelerator, and the mixture was stirred until it became homogeneous. The obtained solution was dropped into 300 mL of ion-exchanged water, and reprecipitation was performed to obtain solid polyimide 2. The weight average molecular weight (Mw) measured by gel permeation chromatography was 300,000, and the polydispersity expressed by weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.0. The fluorine content in the polyimide was 21%.
[0135] Polyimide 3: In a 200 mL glass vial, 60 g of the solvent N,N-dimethylacetamide (DMAC) and 3.8 g (0.012 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) were added and stirred to dissolve TFMB in DMAC. Next, while stirring the contents in the vial, 3.7 g (0.012 mol) of diphenyl-3,3',4,4'-tetracarboxylic dianhydride (s-ODPA) was added over about 5 minutes under a nitrogen gas flow, and the polymerization reaction was carried out by continuing stirring for 6 hours while adjusting the temperature to be in the range of 20 to 40 ° C., thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.00, and the concentration of the polyamic acid solution was 10.0 wt%. Next, 5.9 g of pyridine was added to the polyamic acid solution as an imidization accelerator, and the temperature was kept within a range of 30 to 40°C while stirring. 7.1 g (0.07 mol) of acetic anhydride was slowly added dropwise as an imidization agent over a period of about 10 minutes. The liquid temperature was then further kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. 59.5 mL of DMAC and 59.5 mL of methanol were added to the obtained polyimide solution containing the imidization agent and the imidization accelerator, and the mixture was stirred until it became homogeneous. The obtained solution was dropped into 300 mL of ion-exchanged water, and reprecipitation was performed to obtain solid polyimide 3. The weight average molecular weight (Mw) measured by gel permeation chromatography was 250,000, and the polydispersity expressed by weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.3. The fluorine content in the polyimide was 20%.
[0136] Polyimide 4: In a 200 mL glass vial, 59.5 g of the solvent N,N-dimethylacetamide (DMAC) and 4.7 g (0.188 mol) of 3,3'-diaminodiphenylsulfone (3,3'-DDS) were added and stirred to dissolve 33'-DDS in DMAC. Next, while stirring the contents in the vial, 5.8 g (0.188 mol) of tetracarboxylic dianhydride diphenyl-3,3',4,4'-tetracarboxylic dianhydride (s-ODPA) was added over about 5 minutes under a nitrogen stream, and the polymerization reaction was carried out by continuing to stir for 6 hours while adjusting the temperature to be in the range of 20 to 40 ° C., thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.00, and the concentration of the polyamic acid solution was 14.9 wt%. Next, 5.9 g of pyridine was added to the polyamic acid solution as an imidization accelerator, and the temperature was kept within a range of 30 to 40°C while stirring. 7.1 g (0.07 mol) of acetic anhydride was slowly added dropwise as an imidization agent over a period of about 10 minutes. The liquid temperature was then further kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. 59.5 mL of DMAC and 59.5 mL of methanol were added to the obtained polyimide solution containing the imidization agent and the imidization accelerator, and the mixture was stirred until it became homogeneous. The obtained solution was dropped into 300 mL of ion-exchanged water, and reprecipitation was performed to obtain solid polyimide 4. The weight average molecular weight (Mw) measured by gel permeation chromatography was 210,000, and the polydispersity expressed as weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.5. The fluorine content in the polyimide was 0%.
[0137] Polyimide 5: In a 200 mL glass vial, 60 g of the solvent N,N-dimethylacetamide (DMAC) and 3.8 g (0.012 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) were added and stirred to dissolve TFMB in DMAC. Next, while stirring the contents in the vial, 5.3 g (0.012 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) was added over about 5 minutes under a nitrogen stream, and the polymerization reaction was carried out by continuing stirring for 6 hours while adjusting the temperature to be in the range of 20 to 40 ° C., thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.00, and the concentration of the polyamic acid solution was 10.0 wt%. Next, 5.9 g of pyridine was added to the polyamic acid solution as an imidization accelerator, and the temperature was kept within a range of 30 to 40°C while stirring. 7.1 g (0.07 mol) of acetic anhydride was slowly added dropwise as an imidization agent over a period of about 10 minutes. The liquid temperature was then further kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. 59.5 mL of DMAC and 59.5 mL of methanol were added to the obtained polyimide solution containing the imidization agent and the imidization accelerator, and the mixture was stirred until it became homogeneous. The obtained solution was dropped into 300 mL of ion-exchanged water, and reprecipitation was performed to obtain solid polyimide 5. The weight average molecular weight (Mw) measured by gel permeation chromatography was 210,000, and the polydispersity expressed by weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.2. The fluorine content in the polyimide was 33%.
[0138] Polyimide 6: A 200 mL glass vial was charged with 59.5 g of the solvent N,N-dimethylacetamide (DMAC), 3.819 g (0.012 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB), an aromatic diamine compound having a fluoro group, and 1.105 g (0.0003 mol) of X-22-1660B-3 (Shin-Etsu Silicones), a silicone-modified diamine, and stirred to dissolve the TFMB in the DMAC. Next, while stirring the contents of the vial, 5.576 g (0.013 moles) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) was added under a nitrogen gas flow, and the polymerization reaction was carried out by continuing stirring for 6 hours while adjusting the temperature to be in the range of 20 to 40°C, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.03, and the concentration of the polyamic acid solution was 15% by weight. Next, 3.9 g of pyridine was added to the polyamic acid solution as an imidization accelerator, and the solution was kept at a temperature of 30 to 40°C while stirring. 5.1 g (0.05 mol) of acetic anhydride was slowly added dropwise as an imidization agent. The liquid temperature was then kept at 30 to 40°C and stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution. 59.5 mL of DMAC and 59.5 mL of methanol were added to the obtained polyimide solution containing the imidization agent and the imidization accelerator, and the mixture was stirred until it became homogeneous. The obtained solution was dropped into 300 mL of ion-exchanged water, and reprecipitation was performed to obtain solid polyimide 6. The weight average molecular weight (Mw) measured by gel permeation chromatography was 300,000, and the polydispersity expressed as weight average molecular weight (Mw) / number average molecular weight (Mn) was 4.2. The fluorine content in the polyimide was 28%.
[0139] <Epoxy compounds> The following epoxy compounds 1 to 4 were prepared. Epoxy 1: jER1001 (manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 400-500g / eq, molecular weight 900, softening temperature 64°C) Epoxy 2: XD1000 (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 245-260g / eq, molecular weight 990-1500, softening temperature 68-78°C) Epoxy 3: TEPIC-S (Nissan Chemical Co., Ltd., epoxy equivalent 100g / eq or less, molecular weight 297, softening temperature 100-120°C) Epoxy 4: Epofriend AT501 (manufactured by Daicel Corporation, epoxy equivalent 850-1250g / eq or less, molecular weight 180,000, softening temperature 100°C or more)
[0140] <Other resins> For comparison with the epoxy compound, the following three compounds were prepared. Styrene-acrylic copolymer: ARUFON UC3900 (manufactured by Toa Gosei Co., Ltd.) Polyvinyl butyral compound: S-LEC BL-1 (manufactured by Sekisui Chemical Co., Ltd.) Polyester compound: Vylon 220 (manufactured by Toyobo Co., Ltd.)
[0141] [Examples 1 to 8, Comparative Examples 1 to 9] <Preparation of dry film> Each varnish was prepared by mixing each component with a solvent (dimethylacetamide) according to the composition shown in Table 1 below. The solvent was adjusted so that the amount of solvent was 333 parts by mass per 100 parts of polyimide. Next, the obtained varnish was applied to a polyester film (TN-200, manufactured by Toyobo Co., Ltd.) whose surface had been subjected to a release treatment so that the thickness after drying would be 15 μm, and the resin layer was formed by drying at 80° C. for 30 minutes, and each dry film was produced. The blue dye in Table 1 is Plast Blue 8514 (manufactured by Arimoto Chemical Industry Co., Ltd.).
[0142] The resin layer surface of each dry film was laminated onto the surface of a glass substrate (DragonTrail (registered trademark), manufactured by AGC Inc.) measuring 15 cm in length, 11 cm in width, and 70 μm in thickness. The polyester film was then peeled off from the dry film, and the substrate was heated at 150° C. for 30 minutes to obtain a laminate. For the dry films of Examples 4 to 6, the resin layer surface of the dry film was laminated to a glass substrate using a vacuum pressure laminator (MVLP-500, manufactured by Meiki Seisakusho Co., Ltd.) at an upper and lower hot plate temperature of 90°C and a pressure of 0.5 MPa. After peeling the polyester film from the dry film, a heat treatment was performed at 200°C for 30 minutes to obtain a laminate.
[0143] [Comparative Examples 10 and 11] Each varnish was prepared by mixing each component with a solvent (dimethylacetamide) according to the composition shown in Table 1 below. The solvent was prepared so that the amount of solvent was 333 parts by mass per 100 parts of polyimide. Next, the obtained varnish was applied to a glass substrate (DragonTrail (registered trademark), manufactured by AGC Inc.) measuring 15 cm in length, 11 cm in width, and 70 μm in thickness so that the thickness after drying was 15 μm, and a resin layer was formed by drying at 150° C. for 30 minutes to obtain a laminate.
[0144] <Evaluation of Adhesion> The surface of each laminate obtained was observed from the glass substrate side using a digital microscope (VHX-5000, manufactured by Keyence Corporation). The diameter of the confirmed air bubbles was evaluated in a randomly selected 1 cm square portion of the laminate. The evaluation criteria were as follows: ◎: Air bubble diameter 0mm ○: Bubble diameter 0mm~2mm ×: Air bubble diameter 2mm or more The evaluation results are shown in the following Tables 1 and 2. In Table 1, the notation "-" means that no evaluation was performed.
[0145] <Cross-cut peel test evaluation> Each of the resulting laminates was subjected to a cross-cut peel test evaluation in accordance with ASTM D 3559-B, and the evaluation results were as shown in Tables 1 and 2 below.
[0146] <Warpage evaluation of laminate> Each laminate obtained by heating and drying was left to cool at room temperature for 1 hour, and then the laminate was placed on a flat desk with the glass substrate side facing down, and the warpage values (distance from the desk to the glass substrate) of the four corners of the laminate were measured with a ruler, and the average was taken as the warpage value. The evaluation criteria were as follows: ◎: Less than 8mm ○: 8mm or more and less than 10mm ×: 10mm or more ××:Cannot be rated The evaluation results are shown in Tables 1 and 2 below.
[0147] <Haze's evaluation> The haze (%) of each of the obtained laminates was measured in accordance with JIS K 7136: 2000 using a haze meter (NDH 7000 II, manufactured by Nippon Denshoku Industries Co., Ltd.) The evaluation criteria were as follows. Good: Haze is 2.0% or less ×: Haze is more than 2.0% The evaluation results were as shown in the following Tables 1 and 2. The haze value of the glass substrate itself used in the laminate was 0.35%.
[0148] <Impact resistance evaluation> Each laminate obtained by heating and drying was left to cool at room temperature for 1 hour, after which the laminate was placed on a flat desk with the glass substrate side facing downwards, and an iron ball with a diameter of 30 mm and a weight of 110 g was dropped onto the laminate. The glass after the iron ball was dropped was visually inspected, and the drop height at which cracks were observed was evaluated. The evaluation criteria were as follows: ◎: 50cm or more ○: 40cm or more and less than 50cm △: 30cm or more and less than 40cm ×: Less than 30cm The impact resistance of the glass substrate used in the laminate was evaluated and rated as poor.
[0149] <Surface hardness evaluation> The pencil hardness of the resin layer side of the laminate was measured in accordance with JIS-K5600-5-4:1999, and the highest pencil hardness that did not cause scratches on the coating film was recorded as the pencil hardness. The evaluation results are shown in Tables 1 and 2. The pencil hardness of the glass substrate used in the laminate was 9H.
[0150] [Table 1]
[0151] [Table 2] [Explanation of symbols]
[0152] 1: Dry film 2: Laminate 10: Base material 20: Resin layer 30: Protective film 40: Glass substrate 50: Functional layer 60:Support
Claims
1. A dry film comprising a substrate and a resin layer releasably provided on the substrate, The resin layer is a dry film (excluding those containing boron nitride), characterized in that it contains a polyimide having a fluorine content of 25 mass% or less (excluding polyimide resins containing phenolic hydroxyl groups) and an epoxy compound having an epoxy equivalent of 1000 g / eq or less and a molecular weight of 10,000 or less.
2. 2. The dry film according to claim 1, wherein the polyimide has a YI value of 5.0 or less when the polyimide is formed into a single layer film having a thickness of 50 [mu]m.
3. 3. The dry film according to claim 1, wherein the polyimide has a haze of 2.0 or less when the polyimide is formed into a single layer film having a thickness of 50 [mu]m.
4. The dry film according to any one of claims 1 to 3, wherein the epoxy compound has a softening point of 150°C or less.
5. The dry film according to any one of claims 1 to 4, wherein the epoxy compound is contained in an amount of 1 to 50 mass % based on the total amount of solids in the resin layer.
6. The dry film according to claim 1 , wherein the resin layer further comprises a bluing agent.
7. A laminate comprising a glass substrate and a resin layer provided on one of the main surfaces of the glass substrate so as to be in contact with the surface, A laminate, wherein the resin layer is a resin layer of the dry film according to any one of claims 1 to 6.
8. The laminate according to claim 7 , wherein the glass substrate is chemically strengthened glass.
9. 9. The laminate according to claim 7 or 8, which is used as a cover window for a flexible display element.
10. A method for producing a laminate including a glass substrate and a resin layer provided on one of the main surfaces of the glass substrate so as to be in contact with the resin layer, comprising the steps of: The dry film according to any one of claims 1 to 6 is attached to one of the main surfaces of a glass substrate such that the resin layer of the dry film is in contact with the main surface of the glass substrate; peeling the base material from the dry film to form a resin layer on the glass substrate; The resin layer is heated to a temperature equal to or higher than the softening point temperature of the epoxy compound. A method for producing a laminate, comprising:
Citation Information
Patent Citations
Polymer coated thin glass film substrate
JP2002534305A
New polyimide resin composition and its varnish
JP2008163210A
Polyimide resin composition and thermal conductive adhesive film using the same
JP2015108139A
Reinforced thin glass-polymer laminate
JP2015533685A
Laminate of polyimide and flexible glass
JP2019214159A